The wing on a flea : a book about shapes - Emberley, Ed. (Boston : Little, Brown, 2001)
Simple rhyming text and illustrations guide the reader to see triangles, rectangles, and circles in everyday things.
G2
Keywords: Geometry -- Juvenile literature; Shape; Geometry